2022
DOI: 10.1021/acs.jmedchem.1c01509
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Lead Optimization of Benzene-1,4-disulfonamides as Oxidative Phosphorylation Inhibitors

Abstract: Inhibition of oxidative phosphorylation (OX-PHOS) is a promising therapeutic strategy for select cancers that are dependent on aerobic metabolism. Here, we report the discovery, optimization, and structure−activity relationship (SAR) study of a series of novel OXPHOS inhibitors. The hit compound, benzene-1,4-disulfonamide 1, was discovered in a phenotypic screen selective for cytotoxicity in a galactose-containing medium. Our multi-parameter optimization campaign led to the discovery of 65 (DX3-235), showing n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Our previous study suggested that de-ethylation is a possible metabolic pathway of this series of compounds. 35 We hypothesized that the newly introduced electrodeficient 4,4difluoropiperidine would not likely be a metabolic soft point. Therefore, we designed corresponding sulfones or monosubstituted sulfonamides to address metabolic liabilities.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous study suggested that de-ethylation is a possible metabolic pathway of this series of compounds. 35 We hypothesized that the newly introduced electrodeficient 4,4difluoropiperidine would not likely be a metabolic soft point. Therefore, we designed corresponding sulfones or monosubstituted sulfonamides to address metabolic liabilities.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The filtrate was concentrated and purified with flash chromatography (20% EtOAc in hexane) to give 34 as a yellow solid (520 mg, 91%). 4-(N,N-Diethylsulfamoyl)benzenesulfonyl Chloride (35). To an ice-cooled solution of 34 (100 mg, 0.30 mmol) in a mixture of CH 3 CN (2.5 mL), HOAc (0.16 mL), and H 2 O (0.1 mL) was added 1,3-dichloro-5,5-dimethylimidazolidine-2,4-dione (117 mg, 0.60 mmol) portionwise.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, studies have shown that mTORC1 and other substances can affect glutamine synthetase to inhibit the synthesis of glutamine, further inhibit the nutrient uptake of pancreatic cancer cells, and reduce the proliferation ability of PDAC ( 48 ). At present, DX3-235, DX3-213B and other targeted oxidative phosphorylation inhibitors can effectively inhibit the growth of pancreatic cancer cells in the low nanomolar range and have no obvious toxicity ( 49 ). Therefore, it was believed that targeting the hypoxic microenvironment of PDAC, employing a multimodal therapeutic approach and developing biointegration targets, and remodeling the TME are promising strategies.…”
Section: Discussionmentioning
confidence: 99%